1972
DOI: 10.1073/pnas.69.5.1304
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Sequence of Human apoLp-Gln-II (apoA-II), an Apolipoprotein Isolated from the High-Density Lipoprotein Complex

Abstract: An apolipoprotein, designated by its carboxyl-terminal residue as apoLp-Gln-II, has been isolated from the human high-density lipoprotein family, and its complete aminoacid sequence was determined. The apoprotein, one of the two major apoproteins of this family, is composed of two identical polypeptide chains, each containing 77 amino acids. The two polypeptide chains are connected by a single disulfide bridge at position 6 in the sequence. The minimum molecular v.eight of the intact apoprotein is 17,380. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(80 citation statements)
references
References 24 publications
6
74
0
Order By: Relevance
“…It has been previously pointed out that apoC-III and apoA-II contain several pairs of sequentially adjacent amino acids whose side chains are oppositely charged (38). The ionic interaction of these oppositely charged side chains with the zwitterionic polar head group has been suggested as a mechanism of protein-lipid binding (51).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously pointed out that apoC-III and apoA-II contain several pairs of sequentially adjacent amino acids whose side chains are oppositely charged (38). The ionic interaction of these oppositely charged side chains with the zwitterionic polar head group has been suggested as a mechanism of protein-lipid binding (51).…”
Section: Resultsmentioning
confidence: 99%
“…Human apoAII consists of 2 identical chains linked together by a disulfide bridge. 57 After secretion, apoAII is mainly incorporated into high-density lipoprotein particles containing a variable amount of apoAI and apoAII. 58 The functional role of apoAII in vivo is still unclear, although in vitro and in vivo studies have suggested its proatherogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…ApoA-II and apoC-II were purified as in [17,18]. ApoA-II was dissolved in 6 M guanidine, 0.01 M Tris, 0.1 M NaCI (pH 7.4) and dialyzed against 0.01 M ammonium bicarbonate (pH 8.6).…”
Section: Purification Of Apolipoproteinsmentioning
confidence: 99%